Dancing Hands : A Story of Friendship in Filipino Sign Language - Que, Joanna; Marquez, Charina; Alvarez, Fran (Illustrator); Llagas, Karen (San Francisco : Chronicle Books, 2023)
Sam is fascinated by her new neighbors and their ability to talk with their hands, and when she meets Mai, she starts to learn Filipino sign language so they can communicate. Includes dictionary of Philippine signs.
Keywords: Philippine Sign Language -- Juvenile fiction; Deaf -- Juvenile fiction; Friendship -- Juvenile fiction; Sign language -- Fiction; Filipino Americans -- Fiction; Deaf -- Fiction; People with disabilities -- Fiction; Friendship -- Fiction; Picture books